ENT300 Fruit Crunchy / Ahmad Ruzaini Awang Ahmad... [et.al] - Awang Ahmad, Ahmad Ruzaini; Ijmaen, Muhd. Azwandy; Abang, Muhammad Zulfadli; Majahas, Mestoni (2012)
The name of our company is Fruit Crunchy. This business is form of partnership which consists of six members. Each partner contributes certain amount of capital as agreed in agreement. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Ahmad Ruzaini Bin Ag. Ahmad as the General Manager and Administration Manager, Muhammad Zulfadli Bin Abang as the Marketing Manager, Muhd. Azwandy Bin Ijmaen as the Operational Manager and Mestoni Majahas as the Financial Manager. The selection of General Manager is based on the skill and experience of partner.